Pengaruh Pengembangan Karier Terhadap Kinerja Karyawan (Studi Kasus Mahasiswa Prodi Manajemen Fakultas Ekonomi Universitas Batanghari Jambi) - Indah Selfiani (Science of Management and Students Research Journal (SMS), 2020)
In an organization, career development is very needed to improve employee performance. The study aims to find out, describe, and analyze the influence of career development on employee performance in PT. Nutricia Sari Husada Jambi Branch. The method used is a quantitative descriptive method with independent variable of career development, while the dependent variable is employee performance. The subject of this study is PT. Nutricia Sari Husada Jambi Branch. The sample used in this study is as many as 37 (thirty-seven) people of team elina’s employee working in the company. The analysis tool used is simple linear regression, coefficient of correlation and determination, and hypothesis test. Based on the result of simple linear regression it is indicated that the equation Y = 34,145 + 0,250X. There is a weak relationship between career development and employee performance with correlation value (R) 0,327 and determination value (R2) 0,081 that means career development is only afford to explain the employee performance in the amount of 8,1%, remaining 91,9% are influenced by other variable outside the variable observed. Based on the hypothesis test tcalculated 2,046 ˃ ttable 1,68957. The conclusions of this study indicate that career development have a positive influence and significant that are small on employee performance in PT. Nutricia Sari Husada Jambi Branch.